2012
DOI: 10.1039/c2cc30845b
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical cooperative binary ionic porphyrin nanocomposites

Abstract: Cooperative binary ionic (CBI) solids comprise a versatile new class of opto-electronic and catalytic materials consisting of ionically self-assembled pairs of organic anions and cations. Herein, we report CBI nanocomposites formed by growing nanoparticles of one type of porphyrin CBI solid onto a second porphyrin CBI substructure with complementary functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…A feature of ISA is that it can be used to produce nanomaterials containing porphyrin ions with complementary properties. Examples of such pairings include electron donor and electron acceptor porphyrin ions, 16 light-harvesting and catalytic porphyrin ions, 17 and oppositely-charged catalytic cobalt porphyrin ions. 18 Other potential pairings include the formation of nanomaterials containing Fe and/or Mn porphyrin ions as catalytic components for reactions such as the oxidation of saturated C-H bonds.…”
Section: Ternary Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A feature of ISA is that it can be used to produce nanomaterials containing porphyrin ions with complementary properties. Examples of such pairings include electron donor and electron acceptor porphyrin ions, 16 light-harvesting and catalytic porphyrin ions, 17 and oppositely-charged catalytic cobalt porphyrin ions. 18 Other potential pairings include the formation of nanomaterials containing Fe and/or Mn porphyrin ions as catalytic components for reactions such as the oxidation of saturated C-H bonds.…”
Section: Ternary Nanomaterialsmentioning
confidence: 99%
“…15 ISA is a useful method for preparing porphyrin nanostructures because it can generate materials where the porphyrin ions have complementary properties. These include electron donor and electron acceptor porphyrins, 16 light-harvesting and catalytic porphyrins, 17 or two variants of cobalt porphyrin catalyst for oxygenreduction reactions. 18 ISA has been used to prepare a number of nanoscale structures including nanotubes, 19 nanorods 20 and bundles of nanofibers, 21 as well as micron-sized clovers 16,22 or hyperbranched materials 23 with nanoscale features.…”
Section: Introductionmentioning
confidence: 99%
“…One should note that reported donor-acceptor biomorphs obtained by ionic self-assembly of porphyrins are able to form binary solids referred to as cooperative binary ionic (CBI) solids [73]. Due to their tunable functionalities these materials are promising for applications in solar energy conversion and storage.…”
Section: Other Zinc(ii) Porphyrinsmentioning
confidence: 99%
“…also showed that varying the Sn‐tetra(4‐pyridyl)‐porphyrin tecton (SnTP) to Sn‐tetra(3‐pyridyl)‐porphyrin alters the dimension of the nanotubes from 60 to 35 nm, and also noted a strong dependence of the structure on various axial metals at the core. Such binary ionic porphyrin nanostructures show highly sensitive and transferable optomechanical and photophysical properties in the presence and absence of light, which makes them extremely useful devices for optoelectronic and photonic applications . Another study by Franco et al .…”
Section: Introductionmentioning
confidence: 99%
“…The major drawbacks that hinder the use of binary ionic porphyrin nanostructures for practical applications are the concealed and ambiguous facts about their structures at the atomic level. A number of experimental studies have been published describing the formation of nanostructures from binary ionic porphyrin derivatives leading to stack‐like J‐aggregates and hollow nanotubes. Further, considering the charge disparity of the porphyrin molecules and the presence of alternating H 4 TPPS 4 and SnTPyP layers in the binary ionic nanotubular structures, a theoretical study exploring the molecular organization of ionic porphyrins would be appealing.…”
Section: Introductionmentioning
confidence: 99%